Avaliação da ansiedade, depressão e qualidade de vida dos pacientes com COVID 19 - Oliveira, Alexandre Balsanuf (2022)
Introduction: Physical, emotional, social and environmental aspects have influenced the Quality of Life of the population during the COVID-19 pandemic. In this perspective, the assessment of quality of life has been a topic of interest in the transformation of health care systems, since it assesses the impact of the disease and treatment on the function of patients and on general satisfaction with life. Thus, the general objective of this research is: To analyze the symptoms of anxiety, depression, social support networks and quality of life indicators of people who were infected by COVID-19 in the municipality of Alfenas-MG. Method: This is a cross-sectional study with a quantitative approach, with data collection carried out using the KOBO TOOLBOX application, a free and open software, which took place from March 15 to October 26, 2020. Through a list The sample calculation was carried out by the Health Department of Alfenas-MG, considered as a stratified and proportional random experiment, thus the analyzed sample was of 428 participants. There were losses and the final sample consisted of 217 participants. The data collection instruments were: the Beck Anxiety Inventory (BAI - Beck Anxiety Inventory), the Beck Depression Inventory (BDI-II), the Social Support Scale (EAS) from the Medical Outcomes Study (MOS) called Social Support Scale (MOS-SSS) and the World Health Organization Quality of Life Assessment instrument WHOQOL-Bref. Results: Of the 217 participants, more than 80% reported, even slightly, some anxiety symptom. Data liked that the prevalence of depressive symptoms in this population was low (20%). Data show that, according to Beck's classification, 71.4% of participants have minimal symptoms of anxiety, followed by participants who have mild symptoms (21.7%). Of the total number of participants, only 6.9% reported moderate or severe symptoms of anxiety and depression. According to the Gorenstin classification, the data show that approximately 86% of the participants presented a score considered without anxiety and depression, while 7.4% of the patients can be classified in the dysphoria classification and 6.4% of the patients with classic symptoms of depression. In the analysis of the social support indicators, the observed data that in all dimensions experienced the score was considered high, indicating that in this population there was a coverage of social support. The average regarding quality of life was 3.9, while the controlled average regarding satisfaction with one's own health was 3.8, both characteristics according to the instrument as regular. In this scenario, the most maintained domains were the physical (70.8) and the environment (74.2), suggesting that COVID-19 affected the quality of life of this population. Conclusion: When evaluating the quality of life, it appears that the most compromised domains were the physical aspects and the environment, demonstrating the need for rehabilitation programs and public policies that improve the quality of life of this population.